2019
DOI: 10.1016/j.eatbeh.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and cooking confidence are associated with fruit and vegetable intake in a cross-sectional study with rural women

Abstract: Background-In comparison to their urban and suburban counterparts, midlife and older rural women are less likely to consume adequate fruit and vegetables (F&V). The present study aimed to examine the relationships between psychological, social, and environmental factors and F&V intake among midlife and older rural women in the United States. Methods-This cross-sectional study utilized data from 513 midlife and older rural women (mean age = 67.0, mean BMI = 26.8) living in 22 states. Linear regression models we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…This is consistent with previous qualitative research which emphasised the importance of motivational factors to personalised nutrition (Stewart- Knox et al, 2013;Rankin et al, 2016) and survey research indicating associations between self-efficacy and attitudes and intention to adopt personalised nutrition (Poínhos et al, 2014). This finding is also consistent with research linking self-efficacy to healthy eating (de Borba et al, 2021;Newby et al, 2020;Lo et al, 2019;Churchill et al, 2019;Naughton et al, 2015;Ferranti et al, 2014;Williams et al, 2012;Anderson et al, 2000). That NS-E did not differ between the control and intervention group post-intervention implies it did not impact upon response to the trial and is contrary to previous studies that have observed increased intake of vegetables (Bouwman et al, 2020), increased fruit and vegetable intake (Smith et al, 2020) and reduced fast food consumption (Smith et al, 2020) in response to enhanced self-efficacy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with previous qualitative research which emphasised the importance of motivational factors to personalised nutrition (Stewart- Knox et al, 2013;Rankin et al, 2016) and survey research indicating associations between self-efficacy and attitudes and intention to adopt personalised nutrition (Poínhos et al, 2014). This finding is also consistent with research linking self-efficacy to healthy eating (de Borba et al, 2021;Newby et al, 2020;Lo et al, 2019;Churchill et al, 2019;Naughton et al, 2015;Ferranti et al, 2014;Williams et al, 2012;Anderson et al, 2000). That NS-E did not differ between the control and intervention group post-intervention implies it did not impact upon response to the trial and is contrary to previous studies that have observed increased intake of vegetables (Bouwman et al, 2020), increased fruit and vegetable intake (Smith et al, 2020) and reduced fast food consumption (Smith et al, 2020) in response to enhanced self-efficacy.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this theory, cross-sectional studies in clinical populations (Greiner et al, 2018;Gomez et al, 2018;Hwang, 2016;Ferranti et al, 2014) and apparently healthy populations (Lo et al, 2019;Churchill et al, 2019;Kushida et al, 2017;Swan et al, 2015;Williams et al, 2012;Brug et al, 2006;Anderson et al, 2000) have linked higher self-efficacy to healthier food choices. Greater self-efficacy has been linked to more frequent fruit and vegetable intake (Smith et al, 2020;Lo et al, 2019;Welch and Ellis, 2018;Kushida et al, 2017;Brug et al, 2006), reduced fast food intake (Smith et al, 2020) and less snacking (Churchill et al, 2019). Conversely, lower self-efficacy has been associated less healthy food choices (Williams et al, 2012;de Bruijn and van der Putte, 2009) and low perceived ability to cook healthy food (de Borba et al, 2021).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The MEDAS at baseline was slightly higher in the NIG than in the CIG (8.3 vs. 7.6), but the mixed-effects model analysis allowed for the control of these baseline values. These results confirm that the lack of cooking knowledge and skills is a barrier to dietary modifications [ 33 ], and dietary changes toward healthier eating may be facilitated by the acquisition of greater confidence in cooking [ 34 , 35 ]. However, we have to be cautious with this interpretation considering the small sample size.…”
Section: Discussionsupporting
confidence: 62%
“…[28][29][30] Individuals are more likely to prepare healthful foods at home, as confidence in their cooking abilities increases. [31][32][33] However, lack of time, knowledge, and skill prevent many individuals from preparing meals at home. Through our healthy snacking virtual cooking class, we showed that simple culinary instruction via a videoconference platform trended toward increased confidence in participants' culinary skills, and many felt confident that they would prepare healthful snacks and meals in the future.…”
Section: Discussionmentioning
confidence: 99%